Post Marxist Reading of Leviathan: Sinfield `s Ideology - Fatemeh Kargar Bardaskan; Seyed Hadi Momen (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
The present research shows how a political ideology reading can be perceived by a Post Marxist reading in the Leviathan. In Leviathan, the characters dealt with the important Marxists concepts such as lack of justice and social discrimination and their following effects on people including disillusionment, hopelessness and aimlessness. These effects have stultifying influence on the individuals and make them unaware of their talents and in the end lead them to a life full of misery and hopelessness. Characters and the author himself struggle in a capitalistic society and consciously or unconsciously they are trying at stand against the dominant ideologies and from other hand they themselves are totally dominated by those ideologies and there is no way out, in Leviathan by Paul Auster.